Transformations of British and American Tradition in the Practice of Critical Discourse Analysis - Chizhevskaya, Elena E. (Respectus Philologicus, 2003)
In the present work, an attempt to provide an overview of some important theoretical and methodological aspects of Critical Discourse Analysis is made; central and relevant concepts, terms, and categories of Critical Discourse Analysis are presented.The roots of Critical Discourse Analysis lie in classical rhetoric, text linguistics and sociolinguistics as well as pragmatics.Critical Discourse Analysis is a type of discourse analytical research that primarily studies the way social power abuses, how dominance and inequality are enacted, reproduced and resisted by text and talk in social and political contexts. Critical Discourse Analysis takes an explicit position, and thus wants to understand, expose, and ultimately resist social inequality. The subjects under investigation differ depending on various institutions and scholars who apply Critical Discourse Analysis. Gender issues, issues of racism, media discourses, and political discourses have become very prominent.For Critical Discourse Analysis, language is not powerful in itself – it gains power being used by powerful people. This explains why Critical Linguistics often critically analyses the language use of those in power, who are responsible for the existence of inequalities, and who also have the means and opportunities to improve conditions.In conclusion, theoretical approach is followed by examples (critical analysis of President Bush's political discourse on Iraq question).
Keywords: political discourse; critical discourse analysis; power; intention; persona